Insights on the biochemical and cellular changes induced by heat stress in the Cladocopium isolated from coral Mussismilia braziliensis - Lima, Michele S.; Hamerski, Lidilhone; Silva, Tatiana A.; da Cruz, Maria Luíza R.; Varasteh, Tooba; Tschoeke, Diogo A.; Atella, Georgia C.; de Souza, Wanderley; Thompson, Fabiano L.; Thompson, Cristiane C. (Frontiers in Microbiology, 2022)
Corals are treatened by global warming. Bleaching is one imediate effect of global warming, resulting from the loss of photosynthetic endosymbiont dinoflagates. Understanding host–symbiont associations is critical for assessing coral’s habitat requirements and its response to environmental changes. Cladocopium (formerly family Symbiodiniaceae clade C) are dominant endosymbionts in the reef building coral, Mussismilia braziliensis. The aim of this study was to investigate the effect of temperature on the biochemical and cellular features of Cladocopium. Heat stress generated an increase in O2 and a decrease in total proteins, Chla + Chlc2, hexadecanoic acid- methyl ester, methyl stearate, and octadecenoic acid (Z)- methyl ester. In addition, there was an increase in neutral lipids such as esterified cholesterol and a decrease in free fatty acids that may have been incorporated for the production of lipid droplets. Transmission electron microscopy (TEM) demonstrated Cladocopium cells subjected to heat stress had thinner cell wall, deformation of chloroplasts and increased lipid droplets after three days at 28°C. These findings indicate that termal stress negatively affect Cladocopium spp. with possible short-term impacts for the Mussismilia host nutrition.